Dissecting Market and Business Responses of LQ45 Stocks amidst Crisis: An Event Study of COVID-19 Policies with A Mixed-Method Approach - Pratama, Aditya Firza; Sumirat, Erman Arif; Damayanti, Sylviana Maya (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines how LQ45 companies in Indonesia's capital market responded to government interventions during the COVID-19 crisis, with a focus on the implementation of Large-Scale Social Restrictions (PSBB) and the transition to the New Normal. Employing a mixed-method approach, the study combines event study analysis to examine market reactions and qualitative interviews to explore the internal corporate strategies behind the anomalies of issuers' stock performance. The findings reveal that market resilience and rebound are closely intertwined with macro-policy timing and simultaneously with the internal agility of firms, particularly in managing financial flexibility, operational adaptability, and strategic communication. Quantitative results from an event study reveal significant differences in several indicators regarding before-and-after policy events. At the same time, qualitative insights highlight how firms leveraged crisis moments to adapt and innovate, such as accelerating digital transformation, reinforcing leadership credibility, and institutionalizing organizational learning. Hence, this study contributes to both academic discourse and practical applications by identifying how internal managerial responses shape market dynamics during systemic uncertainty.